Cancer control in small island nations: from local challenges to global action. Issue 9 (September 2019) - Sarfati, Diana; Dyer, Rachel; Vivili, Paula; Herman, Josephine; Spence, Dingle; Sullivan, Richard; Weller, David; Bray, Freddie; Hill, Sarah; Bates, Christopher; Foliaki, Sunia; Palafox, Neal; et al.
Summary: Cancer is a leading cause of death in small island nations and is forecast to increase substantially over the coming years. Governments, regional agencies, and health services of these nations face daunting challenges, including small and fragile economies, unequal distribution of resources, weak or fragmented health services, small population sizes that make sustainable workforce and service development problematic, and the unavailability of specialised cancer services to large parts of the population. Action is required to prevent large human and economic costs relating to cancer. This final Series paper highlights the challenges and opportunities for small island nations, and identifies ways in which the international community can support efforts to improve cancer control in these settings. Our recommendations focus on funding and investment opportunities to strengthen cancer-related health systems to improve sharing of technical assistance for research, surveillance, workforce, and service development, and to support small island nations with policy changes to reduce the consumption of commodities (eg, tobacco and unhealthy food products) that increase cancer risk.